First, add z to both sides of the equation (shown in blue). Then, subtract 2 from both sides (shown in green).
14-z=2
14-zcolor(blue)+color(blue)z=2color(blue)+color(blue)z
14color(red)cancelcolor(black)(-zcolor(blue)+color(blue)z)=2color(blue)+color(blue)z
14+0=2color(blue)+color(blue)z
14=2+z
14color(green)-color(green)2=2+zcolor(green)-color(green)2
14color(green)-color(green)2=2color(green)-color(green)2+z
14color(green)-color(green)2=color(red)cancelcolor(black)(2color(green)-color(green)2)+z
14color(green)-color(green)2=0+z
14color(green)-color(green)2=z
12=z
That's the solution. Hope this helped!